(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This paper presents a passivity-based sliding-mode controller-observer for a two-link lightweight robotic arm that accounts for structural flexibility and payload mass. The system’s dynamical model is obtained using the Euler-Lagrange formalism and the assumed modes method. The resulting mathematical model is highly nonlinear, with strong coupling between the rigid dynamics and the system’s elastic behavior. To achieve accurate trajectory tracking with effective strain elimination, a full-order sliding-mode state observer is designed to estimate the state variables in the presence of parameter uncertainties and external perturbations. Then, the robust observer is combined with a passivity-based controller that uses the estimated states to achieve the desired trajectory, thereby improving system performance and robustness. The stability of the global system is demonstrated using Lyapunov theory and accounting for the passivity property, whereby the total energy is dissipated or stored within the system. The proposed controller/observer is evaluated using MATLAB/Simulink. Simulation results show good trajectory tracking with effective rejection of the external perturbations.